Dissecting the Function of MADS-Box Transcription Factors in Orchid Reproductive Development - Teo, Zhi Wei Norman; Zhou, Wei; Shen, Lisha (Frontiers in Plant Science, 2019)
The orchid family (Orchidaceae) represents the second largest angiosperm family, having over 900 genera and 27,000 species in almost all over the world. Orchids have evolved a myriad of intriguing ways in order to survive extreme weather conditions, acquire nutrients, and attract pollinators for reproduction. The family of MADS-box transcriptional factors have been shown to be involved in the control of many developmental processes and responses to environmental stresses in eukaryotes. Several findings in different orchid species have elucidated that MADS-box genes play critical roles in the orchid growth and development. An in-depth understanding of their ecological adaptation will help to generate more interest among breeders and produce novel varieties for the floriculture industry. In this review, we summarize recent findings of MADS-box transcription factors in regulating various growth and developmental processes in orchids, in particular, the floral transition and floral patterning. We further discuss the prospects for the future directions in light of new genome resources and gene editing technologies that could be applied in orchid research and breeding.